Role of Serum C-Reactive Protein in Predicting Early Anastomotic Leakage After Elective Gastrointestinal Cancer Surgeries - Abdelhamed, Mohamed Aly; Fouad, Mina F.A.; Yousef, Ahmed; Hussein, Alaadin; Abdelmoez, Ahmed (Journal of Neonatal Surgery, 2025)
Purpose: Anastomotic leakage (AL) is the most feared complication after gastrointestinal (GI) cancer surgeries. Early detection can improve patient outcomes. This study examines if C-reactive protein (CRP) can be used as an early predictor of AL in the preclinical stage of post-GI surgeries. Methods: This study included 132 patients subjected to elective GI surgical resections. CRP and albumin levels were checked on POD1 and every other day until discharge or AL development. The diagnostic markers were serial CRP measurements, CRP/albumin ratio, and CRP ratio, which is the ratio between consecutive CRP measurements from POD3 onwards and that of POD1. Results: Twenty patients (15.2%) developed AL. The frequency was 66.7% after pancreaticoduodenal surgery and 2.7 in colorectal tumors was 2.7%. From POD3 CRP, CRP/albumin ratio, and CRP ratio were significantly higher in the leakage patients. On POD3 at a cut-off level of 134.5 mg/L the sensitivity and specificity of CRP were 80% and 64.3%, respectively. The PPV and NPV were low. The CRP ratio was a superior predictor of AL with high specificity and NPV. On POD3, at a CRP ratio cut-off of 1.11, the specificity and NPV were 92.9% and 98.1%, respectively. The readings were 92.9% and 95.4% on POD5, respectively, at a ratio of 0.92. Conclusion: The overall rate of AL after various GI cancer resections was 15.2%, highly influenced by the type of surgery. The low PPV and NPV limit CRP use as a sole predictor of AL. The CRP ratio is a significant tool for ruling out AL based on its high specificity and NPV.